2020
DOI: 10.1002/1438-390x.12063
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of fixed and dynamic heterogeneity to variation in lifetime reproductive success in kestrels (Falco tinnunculus)

Abstract: Many species show large variation in lifetime reproductive success (LRS), with a few individuals producing the majority of offspring. This variation can be explained by factors related to individuals (fixed heterogeneity) and stochastic differences in survival and reproduction (dynamic heterogeneity). In this study, we study the relative effects of these processes on the LRS of a Dutch Kestrel population, using three different methods. First, we extended neutral simulations by simulating LRS distributions of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
(118 reference statements)
1
13
0
Order By: Relevance
“…Paine 1992), we can identify potential candidates by comparing a species’ impact on the population growth of other species to it’s own density (Libralato et al 2006). It is important to note that because our framework allows for asymmetrical interactions, we are able to differentiate a species’ impact on other species from it’s response or sensitivity to neighbours (Broekman et al 2020). Figure 3.B highlights two native species in green which may be potential keystone species due to having strongly competitive effects on the rest of the community overall, despite low densities: Trachymene ornata (TROR) and Gilberta tenuifolia (GITE).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paine 1992), we can identify potential candidates by comparing a species’ impact on the population growth of other species to it’s own density (Libralato et al 2006). It is important to note that because our framework allows for asymmetrical interactions, we are able to differentiate a species’ impact on other species from it’s response or sensitivity to neighbours (Broekman et al 2020). Figure 3.B highlights two native species in green which may be potential keystone species due to having strongly competitive effects on the rest of the community overall, despite low densities: Trachymene ornata (TROR) and Gilberta tenuifolia (GITE).…”
Section: Resultsmentioning
confidence: 99%
“…Firtly, the variable chosen to measure the performance of focal species p may not directly translate into a measure of performance which is relevant to system dynamics, due to inherent practical constraints with collecting empirical data. For example, the life-history reproductive strategies of certain species may lead to measures of high fecundity (or performance) in the field which do not account for low survival rates post-observation (Broekman et al 2020). In these cases, population dynamics models can be used to account for species-specific demographic rates into estimates of interaction effects.…”
Section: Methodsmentioning
confidence: 99%
“…Paine, 1992) and the inclusion of multiple trophic levels, we can identify potential candidates by comparing a species' impact on the population growth of other species to its own density (Libralato et al, 2006). It is important to note that because our framework allows for asymmetrical interactions, we are able to differentiate a species' impact on other species from its response or sensitivity to neighbours (Broekman et al, 2020). Figure 3b highlights a native species in green, Gilberta tenuifolia (GITE), which may be a potential keystone species due to having strongly competitive effects on the rest of the community overall, despite low density.…”
Section: Resultsmentioning
confidence: 99%
“…Arnold and Wade (1984) partitioned reproductive success and Crow’s Opportunity for Selection into sequential episodes of selection and showed that the components are additive only if one includes a residual factor that accounts for all the covariance terms. More recently, several authors interested in distinguishing ‘pluck’ from ‘luck’ (Snyder and Elner 2018) have focused on parsing out the component of LRS that can be attributed to random demographic stochasticity in survival and reproduction (van Daalen and Caswell 2017; Tuljapurkar et al 2020; Broekman et al 2020; Lee et al 2020). All of these approaches can provide useful insights, depending on one’s objectives and the kinds of data that are available.…”
Section: Discussionmentioning
confidence: 99%
“…In their analysis of empirical data for a water-strider, Ferguson and Fairbairn (2001) focused on a similar partitioning: pre-adult survival, adult lifespan, and daily fecundity. Arnold and Wade (1984) Tuljapurkar et al 2020;Broekman et al 2020;Lee et al 2020). All of these approaches can provide useful insights, depending on one's objectives and the kinds of data that are available.…”
Section: Other Ways To Partition Variation In Reproductive Successmentioning
confidence: 99%